Pardon the Interruption: An Integrative Review and Future Research Agenda for Research on Work Interruptions - Puranik, Harshad; Koopman, Joel; Vough, Heather C. (Journal of Management, 2020)
Work interruptions are ubiquitous in today’s workplaces as a result of the proliferation of technology and a growing emphasis on collaboration and open workspaces. Although a large body of research on interruptions has accumulated over the last two decades, this research is scattered across disciplines with little integration. While this fragmentation indicates the complex nature of interruptions, it has also led to inconsistencies in how interruptions are defined and studied. Such differences reduce generalizability of results, lead to conflicting findings, and hinder knowledge development. We present here an integrative review of prior research on work interruptions based on an analysis of 247 publications. As part of the review, we examine prior definitions of interruption and advance a new integrative definition that can anchor a range of future research. We also discuss and summarize the assumptions and implications of the different investigative approaches used to study interruptions. An awareness of these approaches can help scholars better align their theory and investigative approach to adequately capture constructs/relationships of interest. We then synthesize theory and research, across disciplines, to present a process-based model that comprehensively captures our current understanding of how, when, and why work interruptions affect employees in different ways. Lastly, we highlight several avenues in need of more research attention and provide recommendations on how to advance the work interruption literature ahead meaningfully. Our review can act as an important reference for scholars new to interruption research, as well as for established interruption researchers looking to move their research in new directions.